Adsorption characteristics of organosilica based mesoporous materials - Matsumoto A.; Misran H.; Tsutsumi K. (2023)
Hybrid organosilica mesoporous materials with pores of ordered three-dimensional hexagonal structure were prepared by the hydrolysis and co-condensation of 1,2-bis(triethoxysilyl)ethane with various concentrations of a surfactant as structure directing agents. The materials had high pore volume of 1-1.5 mL/g and high surface area from 1057 to 1445 m2/g. Adsorption measurement and adsorption calorimetry revealed that the prepared materials exhibited high hydrophobicity and high affinity toward nonpolar organic vapor such as n-hexane. The dynamic adsorption properties of the materials for n-hexane in the presence of water vapor showed that these hybrid organosilica materials preferentially adsorbed n-hexane vapor and were stable in the presence of water compared to the siliceous MCM48.